Examining critical perspectives on Building Information Modelling (BIM) adoption in New Zealand. Issue 4 (9th July 2020) - Doan, Dat Tien; GhaffarianHoseini, Ali; Naismith, Nicola; Ghaffarianhoseini, Amirhosein; Zhang, Tongrui; Tookey, John
Abstract : Purpose: This research aims to explore the perspectives of the key actors in the New Zealand construction industry towards BIM adoption. Specifically, four themes are examined, including what BIM is; BIM knowledge and understanding; benefits of BIM adoption; and challenges/barriers to BIM adoption. Design/methodology/approach: A qualitative approach using 21 semi-structured interviews with industry experts was adopted. Findings: The results raise a question concerning whether the New Zealand construction industry needs a unique definition of BIM to achieve a clear and consistent understanding amongst construction practitioners. It was found out that most of the construction practitioners in New Zealand are not well aware of BIM, especially the contractors, QSs, supply chain companies and the SMEs. Fourteen potential benefits and ten barriers/challenges to BIM adoption were identified. Individually, time-saving was considered as the most benefit of BIM adoption while BIM understanding was suggested as the most significant barrier by all the interviewees. Originality/value: The research provides valuable insights into BIM understanding as well as recommendations regarding BIM adoption in New Zealand. The results could be considered baseline information for the companies and government to have effective strategies towards BIM adoption. Furthermore, it confirms that characteristics such as benefits and barriers to BIM adoption amongst different countries could be similar. Therefore, it could be useful to analyse the studies, strategies and practices of the pioneer countries in BIM adoption for the implementation.